Haemoglobin and packed cell volume levels in regular and repeat breeding crossbred cows - KUMAR, PAWAN; ROY, G P; AKHTAR, M H; PRASAD, K M; PRASAD, L N (The Indian Journal of Animal Reproduction, 2023)
Haematological attributes (Haemoglobin and packed cell volume) were studied in 85 crossbred cows, which weredivided into six groups. Analysis of variance revealed that there was significant effect of groups on mean haemoglobin ( Hb g %)and packed cell volume (PCV %). On day 0, 16th and 45th ofreproductive stage, the levels ofHb and PCV decreased significantly (p
Keywords: Repeat breeding; Hb; PCV; crossbred cow